2012
DOI: 10.1007/s00216-012-6124-2
|View full text |Cite
|
Sign up to set email alerts
|

Determination of synthetic musk compounds in indoor house dust by gas chromatography–ion trap mass spectrometry

Abstract: A new method for the simultaneous determination of 11 synthetic musks and one fragrance compound in house dust was developed. The nitro musks included musk ketone (MK, 4-tert-butyl-3,5-dinitro-2,6-dimethylacetophenone), musk xylene (MX, 1-tert-butyl-3,5-dimethyl-2,4,6-trinitrobenzene), musk ambrette (1-tert-butyl-2-methoxy-4-methyl-3,5-dinitrobenzene) and musk moskene (1,1,3,3,5-pentamethyl-4,6-dinitroindane). The polycyclic musk compounds were 1,3,4,6,7,8-hexahydro-4,6,6,7,8,8-hexamethylcyclopenta-(γ)-2-benzo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 34 publications
(43 reference statements)
3
15
0
1
Order By: Relevance
“…Several studies have reported the concentrations of synthetic musks in house dusts ( Table 2). The highest concentrations of HHCB, OTNE, and AHTN in dusts from Canada were 31,000, 5600, and 2400 ng/g, respectively (Kubwabo et al, 2012), which were greater than those in house dusts in Japan. The high concentrations of HHCB and AHTN were also found in house dusts from Germany at 11,400 and 3100 ng/g, respectively (Fromme et al, 2004).…”
Section: Synthetic Musks In House Dustsmentioning
confidence: 98%
See 2 more Smart Citations
“…Several studies have reported the concentrations of synthetic musks in house dusts ( Table 2). The highest concentrations of HHCB, OTNE, and AHTN in dusts from Canada were 31,000, 5600, and 2400 ng/g, respectively (Kubwabo et al, 2012), which were greater than those in house dusts in Japan. The high concentrations of HHCB and AHTN were also found in house dusts from Germany at 11,400 and 3100 ng/g, respectively (Fromme et al, 2004).…”
Section: Synthetic Musks In House Dustsmentioning
confidence: 98%
“…This may be due to fast degradation of macrocyclic musks rather than other polycyclic and nitro musks (Suehiro, 1999). Kubwabo et al (2012) reported the occurrence of Musk T in Table 3 Estimated human exposure to Musk T and HHCB by using cosmetics and household commodoties in Japan.…”
Section: Synthetic Musks In House Dustsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, macrocyclic musks have come into greater use in Europe and in North America. Low levels of one macrocyclic musk were found in house dust samples from a Canadian study (Kubwabo et al 2012). Alicyclic musks appeared to be in use at the time we conducted our preliminary screen, but we found very little information on exposure or toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Both HHCB and AHTN have been featured as high production volume (HPV) chemicals by the US Environmental Protection Agency (EPA) and the 2007 OECD (Organization for Economic Co-operation and Development). More than 1000 tons/year of these two chemicals are produced or imported in at least one country/region among the OECD members (Kubwabo et al, 2012;Lu et al, 2011b). Due to their widespread use and low rates of degradation, SMs have been found not only in various environmental matrices (air, water and sediment, etc.…”
Section: Introductionmentioning
confidence: 99%